2013
DOI: 10.1107/s1600536813001281
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorido{N′-[phenyl(pyridin-2-yl-κN)methylidene]isonicotinohydrazide-κ2N′,O}zinc

Abstract: Key indicators: single-crystal X-ray study; T = 293 K; mean (C-C) = 0.006 Å; R factor = 0.042; wR factor = 0.102; data-to-parameter ratio = 14.0.The title compound, [ZnCl 2 (C 18 H 14 N 4 O)], crystallizes with two molecules in the asymmetric unit, which differ in the tautomeric (neutral and zwitterionic) forms of the coordinating organic ligand. In both molecules, the Zn II atom adopts a distorted square-pyramidal geometry by two N and one O atoms of the Schiff base ligand and two Cl atoms acting as monodenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…A value of = 0 indicates an ideal square pyramid and when  = 1, the geometry around the metal center is a perfect trigonal bipyramid. The geometry around each copper(II) ion can be best described as a square pyramidal arrangement as indicated by the Addison's parameter: τ = 0.135 [28] [O1−Cu−N1, 160.35 (9); N2−Cu−Cl1, 168.50 (7); O1−Cu−Cl1, 99.28 (6); N1−Cu−Cl1, 99.42 (7); N2−Cu−O1, 79.74 (10); N2−Cu−N1, 80.72(10)°]. The equatorial plane of the distorted square pyramidal environment around each Cu can be defined by one of the bridging chloride atom, the oxygen atom from one molecule ligand and the two nitrogen atoms (equatorial plane: Cl1, N1, N2, O1; rms mean deviation of 0.082 and Cu 0.1121 (8) away from that plane).…”
Section: Crystal Structures Of Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…A value of = 0 indicates an ideal square pyramid and when  = 1, the geometry around the metal center is a perfect trigonal bipyramid. The geometry around each copper(II) ion can be best described as a square pyramidal arrangement as indicated by the Addison's parameter: τ = 0.135 [28] [O1−Cu−N1, 160.35 (9); N2−Cu−Cl1, 168.50 (7); O1−Cu−Cl1, 99.28 (6); N1−Cu−Cl1, 99.42 (7); N2−Cu−O1, 79.74 (10); N2−Cu−N1, 80.72(10)°]. The equatorial plane of the distorted square pyramidal environment around each Cu can be defined by one of the bridging chloride atom, the oxygen atom from one molecule ligand and the two nitrogen atoms (equatorial plane: Cl1, N1, N2, O1; rms mean deviation of 0.082 and Cu 0.1121 (8) away from that plane).…”
Section: Crystal Structures Of Complexesmentioning
confidence: 99%
“…Versatility coordination to metal [1,2], flexibility in assuming different conformations [3,4], possibility of tautomerism forms [5,6] and possibility of reacting in anionic or neutral forms [7,8], make the study of hydrazones chemistry extremely interesting. The chelating properties of this kind of ligands are diversified by their possible presence in neutral, protonated or deprotonated forms leading of various geometries upon coordination [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The dihedral angle of 9.2°between two fivemembered chelate rings (ZnÀ NÀ CÀ CÀ N and ZnÀ NÀ NÀ CÀ O) shows the non-coplanar nature of the metal-ligand system in 4. [13,18,[47][48][49][50][51] respectively), although in complex 4 the ZnÀ O enolate bond is somewhat longer. The bond angles N6À N5À Zn1 and N9À N8À Zn of 128.9(2)°and 134.8(3)°suggest the bent coordination mode of the azide anions.…”
Section: Crystal Structures Of [Znl 3 (N 3 )] N (3) and [Znl 4 (N 3 )...mentioning
confidence: 96%
“…Cindric et al demonstrated that free benzohydrazone having cytotoxic activity against a THP-1 and HepG2 cell line saw its activity significantly increased after complexation with copper [23]. It is in this context that we have prepared transition metal and lanthanide complexes from ligands having hydrazine units [24][25][26][27][28][29]. In this work, we describe the synthesis and characterization of two complexes of cobalt(II) and copper (II) ions obtained from the N'-(1-(pyridin-2-yl)ethylidene)nicotinohydrazide (HL) ligand, which are characterized by elemental analysis, FT-IR, 1 H NMR, and 13 C NMR.…”
Section: Introductionmentioning
confidence: 96%